2022
DOI: 10.3390/pr10040698
|View full text |Cite
|
Sign up to set email alerts
|

SMEs in Automotive Supply Chains: A Survey on Six Sigma Performance Perceptions of Czech Supply Chain Members

Abstract: Six sigma is understood as a technique for the continuous improvement in process quality; however, it has been rarely scientifically analysed in small- and medium-sized enterprises (SMEs). SMEs representthe vast majority of enterprises throughout economies and contribute to automotive supply chains in various tier ranks. As SMEs are known to lack resources and skills while focusing on short-term benefits rather than on long-term gradual improvements, the aim of of this paper is to analyse the perception of six… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 106 publications
0
3
0
Order By: Relevance
“…Analyzing the data in Table 1 and the four graphs in Figure 8, it was found that, for these reduced values of the step, relatively small different values were obtained, which means that at this level of detail the errors of the method are acceptable, and, therefore, the results obtained for the smallest step (0.01) will be used for interpretation (Figure 9). It is obvious that the results obtained are significantly different from the value of 3400 PPB, which is accepted by most authors [15,23,24,[27][28][29] or disputed by other authors [11][12][13] who do not propose another solution.…”
Section: 𝜎 = √mentioning
confidence: 84%
See 1 more Smart Citation
“…Analyzing the data in Table 1 and the four graphs in Figure 8, it was found that, for these reduced values of the step, relatively small different values were obtained, which means that at this level of detail the errors of the method are acceptable, and, therefore, the results obtained for the smallest step (0.01) will be used for interpretation (Figure 9). It is obvious that the results obtained are significantly different from the value of 3400 PPB, which is accepted by most authors [15,23,24,[27][28][29] or disputed by other authors [11][12][13] who do not propose another solution.…”
Section: 𝜎 = √mentioning
confidence: 84%
“…Since most works dedicated to the Six Sigma concept associate this concept with a maximum shift of 1.5σ and a long-term performance of 3.4 PPM or 3400 PPB [23,24,[27][28][29], it is obvious that this is only a short-term situation (although it is extreme-for the maximum drift), and the following question arises: For a 6σ process (which keeps its standard deviation value unchanged over time, but which naturally has a drift over time, remaining stable), what is the proportion of long-term non-conformities (long-term performance of 6σ processes)?…”
Section: Introductionmentioning
confidence: 99%
“…Table 4 shows the frameworks and their application in supply chain management. The authors highlight as a limitation of the model the non-implementation in the industries due to financial limitations (Cherrafi et al, 2017b;Pfeifer, 2022). The relationship between the manufacturer and its suppliers must be observed and improved so that the benefits of this relationship are transferred to the final customer (Cherrafi et al, 2016;Chiarini & Vagnoni, 2017;Powell et al, 2017a;.…”
mentioning
confidence: 99%